The subgingival microbiomes in periodontitis and health of individuals with rheumatoid arthritis and at risk of developing rheumatoid arthritis. (31st May 2017) - Cheng, Z.; Do, T.; Mankia, K.; Meade, J.L.; Hunt, L.; Nam, J.; Tugnait, A.; Speirs, A.; Clerehugh, V.; Emery, P.; Devine, D.
ABSTRACT: Serum anti-citrullinated protein antibodies (ACPAs), present in 70% of people with rheumatoid arthritis (RA), can be detected ≤10years before the onset of clinical disease. RA and periodontitis are epidemiologically associated and we have reported a high incidence of periodontitis in people who are ACPA+ and at risk of RA. Periodontal bacteria may contribute by multiple routes to the generation of RA-autoantibodies. This study aims to characterise the subgingival microbiomes from periodontitis and health in individuals with/without RA and at risk of RA. Forty-five ACPA+ no RA (RA-at-risk; RAR), 31 healthy controls (HC) and 30 ACPA+ RA patients (RA) underwent a periodontal examination. DNA from subgingival plaque from healthy and deep pocket sites were paired-end sequenced using the Illumina HiSeq3000 and data analysed using MG-RAST + DESeq. Metagenomes in RA samples had high proportions of Actinobacteria; RAR microbiomes contained higher proportions of Bacteroidetes than HC. The relative abundance of P. gingivalis was high in periodontitis and RAR; Aggregatibacter actinomycetemcomitans was detected with similar frequency in each group. Other bacteria implicated in periodontitis and/or autoantibody generation ( Filifactor alocis, Prevotella spp, Leptotrichia spp.) were detected. Analyses are on-going to elucidate the diversity and functional potential of the subgingival microbiome associated with RA.